Leibniz frente al reto spinozista - Cabañas Agrela, Leticia (2014)
Because of his religious and moral convictions, Leibniz was forced to react against Spinoza’s ideas. But at the same time since early youth he had felt strongly attracted to the Spinozist conceptual system. An ambivalent interest for the feared Dutch thinker and his radically new philosophy was the result.